Becoming an evocative coach : a practice guide for the study of evocative coaching and evoking greatness /: a practice guide for the study of evocative coaching and evoking greatness. (2020) - Cash, Jeanie M; Davis-Perry, Donnita; Manthey, George E
No abstract available